Development of a Probic-Based Training Management Framework to Enhance Teachers’ Digital Competence - Iin Iryance; Rita Retnowati; Prihastuti Harsani (Indonesian Journal Publisher, 2026)
The rapid digital transformation in education requires teachers to develop adequate digital competencies to design and implement innovative, effective, and technology-enhanced learning. However, existing professional development programs remain predominantly conventional and have not sufficiently addressed teachers’ needs for sustainable digital competence development. This study aimed to develop a PROBIC (Project Bichronous)-Based Training Management Framework to enhance teachers’ digital competence. The study employed a Research and Development (R&D) method based on the Borg and Gall model, encompassing needs analysis, planning, product development, expert validation, limited field testing, product revision, operational field testing, and final product refinement. Data were collected through observations, interviews, questionnaires, documentation, and digital competence tests. The developed framework demonstrated a high level of validity, achieving validation scores of 98.66% from media experts, 100% from subject-matter experts, and 97% from training management experts, indicating that the framework was highly feasible for implementation. The implementation results also showed improvements in training effectiveness from 89.94% to 94.24%, participant responses from 88.20% to 90.72%, and teachers’ digital competence with an N-Gain score of 76.58%, categorized as effective. The framework particularly enhanced teachers’ digital literacy, the use of digital learning media, online collaboration, and digital content creation. These findings indicate that the PROBIC-Based Training Management Framework is a valid, practical, and effective model for strengthening teachers’ digital competence and supporting sustainable professional development in response to the challenges of digital transformation in education.